THE PRINCIPLES OF PORTRAIT CHARACTERISTICS IN THE NOVELS “PETERSBURG” BY ANDREY BELIY AND “ULYSSES” BY JAMES JOYCE - Turdiboyev, Sanjar (Журнал математики и информатики, 2021)
The article traces the connection between Russian and European literature, which is manifested in the General trend towards updating the worldview at the turn of the 19th and 20th centuries. the principles of portrait characterization are studied in the novels by Beliy and Joyce, within the framework of the theory of receptive aesthetics.